UPAYA PENINGKATAN KEMAMPUAN BERHITUNG DENGAN MEMANFAATKAN MEDIA PEMBELAJARAN MATEMATIKA PADA SISWA/I KELAS I SDN INPRES MELAM HILLI DAN SDN INPRES KEMIRI KABUPATEN JAYAPURA PROVINSI PAPUA - Tiku Tandiangnga; Diana Setyaningsih (LPPM Uncen, 2019)
The learning media can be interpreted as all objects that mediates in the occurrence of learning. Based on its function, the learning media can be tools and medium. Tools are the learning media containing or bring the characteristics of the concepts of the studied. While medium is the learning media who has main function as a tool for learning. The purpose of the activity is to increase the capabilities of mathematics calculation of the first grade student at SDN Inpres Melam Hilli and SDN Inpres Kemiri about the concept of counting operation by utilizing the learning media. The counting operation intended in this activity are defined as the concept of the sum and reduction of natural number from 1 to 20. The methods used in activity are lecturing method, asking questions method, and gaming method. In this activity two types of the games are done, which are papan saku game and tali pas game to embed the concept of counting operation. After this two games are done, the students directed to complete LKS I and II. The success indicator that the students understand the material about counting operation by utilizing mathematics learning media is that they can complete LKS with a value more than or equal to 70. The impact of this activity is the students are very excited in following the activities ranging from the introduction, delivery of the material accompanied by papan saku game ang tali pas game, until the evaluation. On the evaluation phase most of the students quite understand the material that has been delivered and complete LKS with value more than or equal to 70. This means, the utilization of learning media with the gaming method could increase the value of learning/the capabilities of mathematics calculation of the students, especially at counting operation material. Keywords: mathematics learning media, counting operation, gaming method